An exploration of the cognitive mechanism underlying general risk-aversion in obsessive-compulsive disorder : the construction and validation of the multi-dimensional risk-assessment scale - Garratt-Reed, David (Curtin University, 2012)
Individuals with OCD avoid minor risks that are unrelated to their obsessive fears and this general risk-aversion is implicated in treatment failure and relapse. However, a lack of understanding of the cognitive biases driving general risk-aversion has hampered therapeutic efforts to address this problematic cognitive-behavioural pattern. This research was designed to advance understanding of these cognitive biases in order to potentially improve treatment outcomes for individuals with OCD.Perception of threat is a significant causal factor in risk-aversion and this research was designed to investigate the cognitive biases driving threat overestimation, and consequent risk-aversion, in general situations among individuals with OCD. Beck, Emery, and Greenberg’s (1985) model of threat perception formed the theoretical basis for this investigation. This model states that threat perception and consequent anxiety within a situation are the result of cognitive computations involving the perceived probability and perceived cost of potential negative events, along with perceived ability to cope with those events. However, no validated scales existed to measures these constructs, so the first undertaking in this research was to create the Multi-Dimensional Risk Assessment Scale (MDRAS) to perform this important task.The aim of Study 1 was the development of the MDRAS, a scale designed to assess perceptions of the probability and cost of specific negative events, as well as perceived ability to cope with those events. The events selected were unrelated to typical OCD concerns and include some everyday risks as well as some risks that are situated in the future. Items were generated based on items from two existing scales, the Everyday Risk Inventory-Australian Revision (ERI-AUS, Cicolini & Rees, 2003) and the Social Readjustment Rating Scale (SRRS, Holmes & Rahe, 1967). Two hundred and twenty two non-clinical participants, consisting of students at Curtin University and community members recruited through snowball sampling, completed the 19-item MDRAS. Principal components analyses (PCA) revealed that the MDRAS conformed to its intended factor structure, with the Probability, Cost, and Coping scales containing two factors relating to everyday risks and future risks. However, several items did not load as planned and were removed from the scale.A second PCA demonstrated that the shortened, 14-item version of the MDRAS contained 7 items assessing threat perceptions for everyday risks, and 7 items assessing threat perceptions for potential future risks. Confirmatory factor analysis (CFA) indicated that, in addition to two subordinate factors, Total Probability, Total Cost, and Total Coping scores could also be interpreted. As intended, the MDRAS appears to assess perceived probability and cost of potential negative daily and future events, and perceived ability to cope with those events.In Study 2 the pattern of relationships between the MDRAS scales and a measure of negative affect, a measure of obsessive beliefs, and a measure of perceived control was examined. Participants were the same individuals who had participated in Study 1. They completed the Positive and Negative Affect Schedule (PANAS; Watson, Clark, & Tellegen, 1988), the Obsessive Beliefs Questionnaire (OBQ; OCCWG, 2005), and the Anxiety Control Questionnaire (ACQ; Rapee, Craske, Brown, & Barlow, 1996) in addition to the MDRAS. Results provided evidence for the internal consistency as well as the convergent and discriminant validity of the MDRAS scales. It was concluded that the MDRAS appears to be a reliable and valid measure of perceptions of the probability and cost of negative events, and of perceived ability to cope with those events.In Study 3 MDRAS scores were compared among 21 individuals with OCD, 17 anxious controls, and 29 non-anxious controls. Participants completed the MDRAS and the PANAS in addition to a measure of obsessive symptoms – the Obsessive-Compulsive Inventory-Revised (OCI-R; Foa et al., 2002). Analyses of variance (ANOVAs) indicated that individuals with OCD perceived a higher cost of negative events and perceived their ability to cope with those events as lower than did non-clinical individuals. This was true for both the MDRAS Total Cost and Coping scales, as well as for the Everyday and Future Cost and Coping Scales, with medium to large effect sizes in each case. However, individuals with OCD did not estimate a higher probability of the occurrence of everyday or future negative events than did non-clinical individuals. This indicates that general risk-aversion among individuals with OCD is driven by inflated cost and reduced coping ability estimates. However, ANCOVAs revealed that, after controlling for negative affect, there were no differences between the OCD and the non-anxious groups on any of the MDRAS scales.This suggests that negative affect, rather than OCD specifically, is related to cost and coping ability biases, and consequent risk-aversion. In addition, ANOVAs revealed that the OCD group did not score differently from the anxious controls on any MDRAS scale, suggesting that all anxious individuals are likely to perceive heightened levels of cost associated with general negative events, and demonstrate low subjective ability to cope with those events. This is consistent with theories suggesting that general risk-aversion is a transdiagnostic risk factor for anxiety in general, rather than any specific diagnosis (Maner & Schmidt, 2006). It was concluded that individuals with OCD are risk-aversive because they overestimate the cost of potential negative events, and underestimate their ability to cope with those events. However, a similar conclusion was drawn for other anxious individuals and there was no evidence that general risk-aversion is a phenomenon specific to OCD.It was concluded that general risk-aversion is likely to be an important target for treatment across anxiety disorders and it would seem prudent to target biased estimates of the cost of negative events, and/or perceived ability to cope with those events, in order to reduce threat perception and general risk-aversion among anxious individuals. Methods for achieving this were discussed. In addition, it was concluded that the MDRAS has the potential to be a useful research and clinical tool for assessing the cognitive biases involved in threat overestimation and consequent risk-aversion among anxious individuals.